Seasonal Distribution and Diversity of Non-Insect Arthropods in Arid Ecosystems: A Case Study from the King Abdulaziz Royal Reserve, Kingdom Saudi Arabia - Taghreed A. Alsaleem; Moutaman Ali Kehail; Abdulrahaman S. Alzahrani; Turki Alsaleem; Areej H. Alkhalifa; Abdulaziz M. Alqahtani; Mohammed H. Altalhi; Hussein H. Alkhamis; Abdullah M. Alowaifeer; Abdulwahed Fahad Alrefaei (Biology, 2024)
The biodiversity of invertebrate animals is largely affected by climatic changes. This study evaluates the seasonal abundance and diversity of non-insect arthropods in the King Abdulaziz Royal Reserve (KARR), Saudi Arabia, over four collection periods (summer, autumn, winter, and spring) during 2023. Sampling was conducted across multiple sites in the reserve using both active (manual collection and active surveying for the diurnal species) and passive (pitfall traps and malaise traps for the nocturnal species) methods. A total of 586 non-insect arthropod specimens were collected, representing four classes: Arachnida, Chilopoda, Branchiopoda, and Malacostraca. The results show that the most abundant species was the jumping spider Plexippus paykulli, which dominated collections across two seasons, with a peak abundance of 50.7% in late summer. Seasonal variations in non-insect arthropod diversity were observed, with a lower diversity recorded during January–March (4 species, and this may be attributed to this period revealing the lowest temperature reading recorded during the study period) and higher diversity in August–September (end of summer) and October–November (mid of autumn), with 14 species. Scorpions, particularly species from the families Buthidae and Scorpionidae, were common during the summer months, while solifuges and centipedes showed sporadic occurrences across seasons. These findings align with the results for arthropod distribution in arid regions, with temperature and resource availability as key drivers of biodiversity in desert environments because of their direct effects on the biochemical processes of these creatures. This study contributes valuable baseline data on the non-insect arthropod fauna of the KARR. The insights gained from this study can aid in conservation efforts and provide a foundation for further research on non-insect arthropod ecology in arid landscapes.